Strand 2: The dynamics of Internet supported team learning: A case study - Huysman, Marleen; Gerrits, Han (Proceedings of the International Conference on Networked Learning, 1998)
This paper contributes to the discussion on information and communication technology (ICT) for educational purposes. Research was done on the use of a virtual learning environment (VLE) based on Internet technology during a practical course for economic students at the Vrije Universiteit Amsterdam. The VLE Internet has been used for many different purposes such as to support team learning, to inform students about course-specific issues, to support communication between students, to create and maintain websites, to publish students’ results on these websites, and to evaluate the assignments. The paper discusses the various learning and reaching processes that cook place and the influence of using the VLEinternet on these processes. It is argued that the use of the VLEinternet for educational purposes is very dynamic as it might influence learning and teaching in various different ways.